Mercury-selenium relationships in liver of Guiana dolphin: the possible role of Kupffer cells in the detoxification process by tiemannite formation. - José Lailson-Brito; Renato Cruz; Paulo Renato Dorneles; Leonardo Andrade; Alexandre de Freitas Azevedo; Ana Bernadete Fragoso; Lara Gama Vidal; Marianna Badini Costa; Tatiana Lemos Bisi; Ronaldo Almeida; Dario Pires Carvalho; Wanderley Rodrigues Bastos; et al. (PLoS ONE, 2012)
Top marine predators present high mercury concentrations in their tissues as consequence of biomagnification of the most toxic form of this metal, methylmercury (MeHg). The present study concerns mercury accumulation by Guiana dolphins (Sotalia guianensis), highlighting the selenium-mediated methylmercury detoxification process. Liver samples from 19 dolphins incidentally captured within Guanabara Bay (Rio de Janeiro State, Brazil) from 1994 to 2006 were analyzed for total mercury (THg), methylmercury (MeHg), total organic mercury (TOrgHg) and selenium (Se). X-ray microanalyses were also performed. The specimens, including from fetuses to 30-year-old dolphins, comprising 8 females and 11 males, presented high THg (0.53-132 µg/g wet wt.) and Se concentrations (0.17-74.8 µg/g wet wt.). Correlations between THg, MeHg, TOrgHg and Se were verified with age (p<0.05), as well as a high and positive correlation was observed between molar concentrations of Hg and Se (p<0.05). Negative correlations were observed between THg and the percentage of MeHg contribution to THg (p<0.05), which represents a consequence of the selenium-mediated methylmercury detoxification process. Accumulation of Se-Hg amorphous crystals in Kupffer Cells was demonstrated through ultra-structural analysis, which shows that Guiana dolphin is capable of carrying out the demethylation process via mercury selenide formation.